2006
DOI: 10.1002/mc.20272
|View full text |Cite
|
Sign up to set email alerts
|

Pinocembrin triggers Bax‐dependent mitochondrial apoptosis in colon cancer cells

Abstract: Bioflavanoids are the major pigments in plants with multitude of biological activities including inhibition of proliferation or induction of apoptosis in tumor cells. Even though the safety records of most flavanoids are exceptional, its therapeutic use is still in its infancy. We have isolated pinocembrin (5,7-dihydroxyflavanone) from Alpinia galanga that showed cytotoxicity against a variety of cancer cells including normal lung fibroblasts with relative nontoxicity to human umbilical cord endothelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…The rates of depletion of mitochondrial membrane potential were 84.02 ± 1.33% and 71.21 ± 1.74% in the cells treated with 100 and 150 µM of pinocembrin, respectively, for 24 h as compared to 96.12 ± 0.43% in the control group (Figure 6). These results are similar with previously reported studies in colon cancer (Kumar et al, 2007).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The rates of depletion of mitochondrial membrane potential were 84.02 ± 1.33% and 71.21 ± 1.74% in the cells treated with 100 and 150 µM of pinocembrin, respectively, for 24 h as compared to 96.12 ± 0.43% in the control group (Figure 6). These results are similar with previously reported studies in colon cancer (Kumar et al, 2007).…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, the cells become round-shaped and poorly adhered to the cultured plates while the control group cells showed a typical polygonal and cobblestone monolayer appearance and remained firmly attached to cultured plates (Figure 3). The results revealed that pinocembrin induced growth inhibition of LNCaP cells, in addition to other type of cancer cells previously reported including colon cancer (Kumar et al, 2007;Pan et al, 2011;Zizic et al, 2013) and leukemia (Hsu et al, 2010;Salahdeen and Murtala, 2012). …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…3a); however, at doses higher than 50 mg/L, PIN inhibited EPC proliferation, which might be due to the fact that PIN at higher doses promote EPCs apoptosis (Kumar et al 2007). Similar dose-dependent effects of PIN on the migratory, adhesion and tube-forming abilities of EPCs were observed (Fig.…”
Section: Pinocembrin Affects the Biological Functions Of Epcsmentioning
confidence: 99%
“…A recent study found that low-doses of PIN provide acute neurovascular protection in a glutamate injury model partly through the inhibition of p53 expression and cytochrome c release and by changing the Bax/Bcl2 ratio (Gao et al 2008). High doses of PIN induce mitochondrial apoptosis in a variety of cancer cells but are nontoxic to human umbilical cord endothelial cells (Kumar et al 2007). Our previous study found that PIN treatment significantly reduced atherosclerotic plaque area, plasma lipid levels, and increased the levels of plasma NO in apoE -/-mice fed a high-fat diet for 14 weeks.…”
Section: Introductionmentioning
confidence: 99%